Dostęp kobiet i mężczyzn do studiów wyższych. Studium porównawcze = The access of women and men to higher education. A comparative study - Gromkowska-Melosik, Agnieszka (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The essence of the problem of women equality with reference to their access to higher education has undergone a substantial overhaul in the last decade. In the quantity context, it is difficult to refer to the idea of women`s discrimination; just the opposite - among the students` population as a whole, women are gaining a growing majority. In connection with the above, the majority of analyses concentrate on differences in the prestige of higher education institutions having both sexes as students, as well as on the choice of studies (specialisation) determined by the sex difference. The article deals with the diagnosis of the significant increase of educational aspiration of women, being an issue for the last decades.
Keywords: szkolnictwo wyższe; kobiety; mężczyźni; równość